I See Dead People: Examining the Admissibility of Living-Victim Photographs in Murder Trials - Rychlak, Susanna (2016)
In the summer of 2015, the Tennessee legislature debated and passed the Victim Life Photo Act, which went into effect on July 1, 2015. This law states: In a prosecution for any criminal homicide, an appropriate photograph of the victim while alive shall be admissible evidence when offered by the district attorney general to show the general appearance and condition of the victim while alive. Victims' rights groups lobbied for this and similar laws throughout the country, which were then enacted by state legislatures. Though these laws amended rules of evidence, the considerations under which they were passed were largely normative, emotional, and based on concerns for victims' families in the trial process. In general, living-victim photographs have very low relevance. Often the only issues they demonstrate in a homicide case are the identity of an individual and that he or she was once alive, neither of which is often contested. Thus, with little to no relevance, in-life photos are often introduced into evidence for the same reason that these laws were passed: to humanize the victim, appease grieving family members, and elicit emotions of bias, sympathy ... [and] retribution in the jury. As such, these photographs would be-and often have been- excluded from evidence during a trial as lacking relevance or being unfairly prejudicial under a Rule 403 balancing test. New waves of state legislation, however, have eviscerated these balancing considerations, taking admissibility determinations out of the hands of judges and legislatively mandating that these photos be admissible